2022
DOI: 10.3390/genes13122399
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X-Associated Neuropsychiatric Disorders (FXAND) in Young Fragile X Premutation Carriers

Abstract: Background: The fragile X premutation carrier state (PM) (55–200 CGG repeats in the fragile X messenger ribonucleoprotein 1, FMR1 gene) is associated with several conditions, including fragile X-associated primary ovarian insufficiency (FXPOI) and fragile X-associated tremor ataxia (FXTAS), with current literature largely primarily investigating older PM individuals. The aim of this study was to identify the prevalence of fragile X-associated neurodevelopmental disorders (FXAND) in a sample of young PM individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…However, these findings are constrained by clinic-based or small sample sizes. To ascertain the accurate prevalence of ASD in PM carriers, larger population cohort studies are essential, given the limited scope of current research utilizing clinic-based or small-sample approaches [ 37 , 39 , 41 , 42 , 56 ]. Although no studies have systematically studied the prevalence of ASD in adult PM carriers, evidence points towards elevated rates of the broad autism phenotype (BAP) in the PM.…”
Section: Fxpac and Relationships With Genetic Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these findings are constrained by clinic-based or small sample sizes. To ascertain the accurate prevalence of ASD in PM carriers, larger population cohort studies are essential, given the limited scope of current research utilizing clinic-based or small-sample approaches [ 37 , 39 , 41 , 42 , 56 ]. Although no studies have systematically studied the prevalence of ASD in adult PM carriers, evidence points towards elevated rates of the broad autism phenotype (BAP) in the PM.…”
Section: Fxpac and Relationships With Genetic Markersmentioning
confidence: 99%
“…These findings have led to further studies of problems that occur in carriers before the onset of FXTAS and of disorders that can occur even in childhood in a subgroup of carriers. Although most carriers have normal intellectual abilities and are without neuropsychological issues, studies have shown that a subgroup of carriers have psychiatric problems in childhood, including anxiety [ 36 ], attention deficit hyperactivity disorder (ADHD) [ 37 , 38 ], social deficits [ 39 ], and even autism spectrum disorder (ASD) [ 37 , 40 , 41 , 42 ]. For carriers who experience seizures, there is a higher incidence of ASD or intellectual disabilities (ID) compared to carriers without seizures [ 43 ], and 20% of carriers with ID and ASD have a second genetic hit, as detected with whole-exome sequencing (WES) or microarray studies [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, our results suggest that AR-Sb would be useful in assessing the risk of specific psychiatric conditions, including depression, sleep disorders, ADHD, ASD, and anxiety symptoms, including social avoidance, interpersonal sensitivity, shyness, eye contact avoidance, social phobia, panic disorders, etc., which are common in PM carriers [ 2 , 53 ]. In addition, co-occurring FXAND-related conditions in carriers of PM alleles are also very common, with a higher prevalence of depression and anxiety [ 2 , 54 ]. Depression is more frequently reported in young carriers than in a matched control group [ 55 ], as well as in female than in male carriers of PM alleles [ 2 , 56 , 57 ], and is directly related to the number of CGG repeats [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings are constrained by clinic-based or small sample sizes. To ascertain the accurate prevalence of ASD in PM carriers, larger population cohort studies are essential, given the limited scope of current research utilizing clinic-based or smallsample approaches [37,39,41,42,56]. Although no studies have systematically studied the prevalence of ASD in adult PM carriers, evidence points towards elevated rates of the broad autism phenotype (BAP) in the PM.…”
Section: Autism Spectrum Disorder (Asd) and The Broad Autism Phenotyp...mentioning
confidence: 99%